The Philosophy of Social Market Economy: Michel Foucault's Analysis of Ordoliberalism - Nils Goldschmidt; Hermann Rauchenschwandtner (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2007)
Michel Foucault's lectures at the Collège de France in 1978-1979 centered on the analysis of power with regard to liberalism. Foucault especially focused on German ordoliberalism and its specific governmentality. Although Foucault's review of the ordoliberal texts, programs, and books is very faithful, there are some occasional "schematic" simplifications. Our paper will evaluate Foucault's constitution of an ordoliberal "archive", though more emphasis will be put on the general importance of the phenomenological orientation in Walter Eucken's work. Hence, three tasks will guide our paper: first, an analysis of Foucault's position; second, the phenomenological foundation of the ordoliberal discourse compared to the 18th century liberal discourse, i.e. the way in which Walter Eucken received Husserl. Third, our paper shall raise the subject of the mutual historical-epistemological complementation of philosophy and economics by taking Foucault's analysis as the starting point. Furthermore, the consequences of a phenomenological, "eidetic" order of the economy will be discussed, focusing mainly on the expansion of competition in social domains.
Keywords: 330; Foucault; Husserl; Eucken; ordoliberalism; eidetic order of the market; social market economy; Ordoliberalismus; Wirtschaftsphilosophie; Soziale Marktwirtschaft; Theorie; Michel Foucault